(untitled) (Journal of the College of Education for Women, 2021)
The aim of the research is to demonstrate the concept, characteristics, efficiency and adequacy of infrastructure in Khor Al-Zubair, as it represents an important benchmark for judging the development of the city. The researchers thus aim to measure the efficiency, adequacy and personal impression of each service in Khor Al-Zubair city and its residential neighborhoods. To meet this objective, the researchers used the descriptive and analytical approach that involves randomly distributing a questionnaire with specific questions to the neighbors of the city. The study has reached a set of results and recommendations that contribute to addressing the problems to the sector of infrastructure services in the city, such as: the per capita share of liquid water in Khor Al-Zubair has reached 100 liters/day, which is less than the quota specified, 450 liters/day by the Iraqi standard. This results in a deficit of 77.2% of the total amount of water that must be provided per person. In addition to the deficiency there is also a decrease in the quality of liquefied water in Khor Al-Zubair city due to its high level of salinity in it, which reached 916 TDS in 2020. Further, there is a deficit of electrical power of 10 megawatts, leading the city to be exposed to regular interruption of electrical current of about six hours per day, where the hours of interruption increase in the hot season of the year.